2005
DOI: 10.2190/x36m-f7xq-penb-rfbf
|View full text |Cite
|
Sign up to set email alerts
|

What is the Meaning of Life? Women's Spirituality at the End of the Life Span

Abstract: Spiritual exploration often occurs after the loss of a significant other or with the impending death of oneself. Twenty-six older women were intensively interviewed; none had experienced a recent loss or terminal illness. Many wanted to understand their place in the order of things and were not looking to organized religion for answers. Dominant themes that emerged from the interviews included: a need to feel connected; spiritual questioning; existential angst; thoughts about death and dying; and, to a lesser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In qualitative research regarding meaning in life, older persons speak about their losses, their struggle to overcome fear and depressive feelings, and the way they create meaning in adversity. 18,79,80 Especially when negative circumstances have impact on a highly valued social role, for example, mother or friend, it is difficult to find new meaning in life. 87 Older persons adapt to the negative situation based on their coping styles and using different coping strategies: Coping styles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In qualitative research regarding meaning in life, older persons speak about their losses, their struggle to overcome fear and depressive feelings, and the way they create meaning in adversity. 18,79,80 Especially when negative circumstances have impact on a highly valued social role, for example, mother or friend, it is difficult to find new meaning in life. 87 Older persons adapt to the negative situation based on their coping styles and using different coping strategies: Coping styles.…”
Section: Resultsmentioning
confidence: 99%
“…Through the way individuals create or discover meaning, they connect with self, others, and with something greater than oneself. 17,52,79 Meaning-finding is not an individual matter, it is interacting with society. 8,54,66,68,72,73,75,94 In our image of the river, the river does not exist on its own, but is part of nature, the universe, for example, connected with clouds, the earth, vegetation, and animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be argued that women's lives involve a series of transitions through aging, family development, and other unexpected life events (R. L. Harris et al, 1986;Reinke et al, 1985). Exploring the meaning of religion and spirituality among older adult women (aged 55 and above), Moremen (2005) found that women used their spirituality as a venue for connection to the self, others, and the world, as well as a method of placing themselves in the greater context of the world. Among menopausal women, Steffen (2011) identified spiritual strength as a correlate of lower menopausal symptoms and higher adaptive coping.…”
Section: Religion/spirituality Identity and Sense Of Selfmentioning
confidence: 99%
“…The terms most often used have to do with the notion that there is "meaning making" that occurs at the end of life (Meyer, 1998). The studies done by nurses, chaplains, psychologists, and social workers are almost always qualitative studies with fewer than 20 interviews (McGrath, 2003;Kaut, 2002;Moremen, 2004).…”
Section: Introductionmentioning
confidence: 99%